Primary Prevention of Childhood Obesity: An Interdisciplinary Analysis - Hilbert, Anja (Obes Facts, 2008)
The primary prevention of childhood obesity requires combined efforts by stakeholders at various societal levels, based on the knowledge from multiple disciplines. The goal of the present study was therefore to analyze current preventive approaches and delineate implications for future prevention research and practice by integrating knowledge from genetics, law, economics, psychology, and social ethics. Inconclusive evidence on the etiology of obesity, a complex, multifactorial condition, likely complicates prevention, leading to a lack of specificity regarding target groups, focus, and techniques. It is recommended to increase the specificity of prevention by explicitly considering risk factor evidence, including evidence on genetic factors. Because the institutional and legal framework of primary obesity prevention in children is insufficient in many countries, considering the risk factors for childhood obesity is also crucial for establishing a basis for legal regulations. Companies from sectors concerned with food intake and physical activity may be involved in preventive action, e.g., for initiating self-defeating sanctions. Long-term behavior change may be enhanced through the systematic application of behavior modification techniques within primary prevention programs. Overall, an interdisciplinary perspective furthers understanding of the complexity of this condition and can inform public health strategies on the primary prevention of childhood obesity.